2008
DOI: 10.1007/s10903-008-9191-x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes Among Foreign-Born and US-Born Chinese Americans, 1995–2000

Abstract: This paper examines nativity differences in adverse perinatal outcomes of Chinese-American mothers. Singleton live births to US-resident Chinese women (150,620 foreign-born, 15,040 US-born) and a random sample of 150,620 non-Hispanic White mothers were selected from 1995 to 2000 national linked birth/infant death certificate files. Associations between maternal nativity status and adverse perinatal outcomes were assessed using multivariable logistic regressions. Compared to US-born Chinese mothers, foreign-bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…While this is the first study, of which we are aware, that has directly assessed differences in the relationship between PNC use and PTB risk between foreign and USborn mothers overall, our findings are supported by other studies that have shown similar results among particular ethnic minority groups in the US [9,11,[17][18][19][20]. Of particular interest is a study by Singh and Yu [11] that demonstrated that among all births in the US between 1985-1987, the prevalence of failure to use PNC was higher among foreign-born mothers, although foreign-born mothers had lower risk for infant mortality, low birth weight, and PTB.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…While this is the first study, of which we are aware, that has directly assessed differences in the relationship between PNC use and PTB risk between foreign and USborn mothers overall, our findings are supported by other studies that have shown similar results among particular ethnic minority groups in the US [9,11,[17][18][19][20]. Of particular interest is a study by Singh and Yu [11] that demonstrated that among all births in the US between 1985-1987, the prevalence of failure to use PNC was higher among foreign-born mothers, although foreign-born mothers had lower risk for infant mortality, low birth weight, and PTB.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, several studies suggest that PNC may be less important as a predictor of PTB risk among foreign-born mothers as compared to US-born mothers [9,[17][18][19][20]. However, to our knowledge, there are no studies in the peer-reviewed literature that have systematically assessed differences in the relation between PNC and PTB risk by maternal nativity.…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in LBW between racial/ethnic groups in the US are well documented in both local (Almeida, Mulready-Ward, Bettegowda, & Ahluwalia, 2014; Chang, Hurwitz, Miyamura, Kaneshiro, & Sentell, 2015; Kieffer, Mor, & Alexander, 1994; Qin & Gould, 2010; Sanchez-Vaznaugh et al, 2016) and national (Acevedo-Garcia, Soobader, & Berkman, 2005, 2007; Le, Kiely, & Schoendorf, 1996; Li, Keith, & Kirby, 2010; Singh & Yu, 1996; Sparks, 2009) studies, even after controlling for socioeconomic status (SES). Previous literature has suggested that variations in size at birth among racial/ethnic groups are in large part due to environmental factors, such as nutrition and the psychosocial stress associated with discrimination and institutional racism, rather than genetic factors (Geronimus, 1996; Papageorghiou et al, 2014; Sparks, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has suggested that variations in size at birth among racial/ethnic groups are in large part due to environmental factors, such as nutrition and the psychosocial stress associated with discrimination and institutional racism, rather than genetic factors (Geronimus, 1996; Papageorghiou et al, 2014; Sparks, 2009). Accumulating, but not conclusive, evidence from local (Howard, Marshall, Kaufman, & Savitz, 2006; Qin & Gould, 2010) and national studies (Acevedo-Garcia et al, 2005, 2007; Le et al, 1996; Li et al, 2010; Singh & Yu, 1996) suggests differential associations between LBW and maternal birthplace within racial/ethnic groups, with studies reporting that foreign-born Hispanics, as well as Asians and non-Hispanic blacks, have a lower risk of LBW compared with their US-born racial/ethnic counterparts. Lower risk of LBW is observed in these immigrant groups despite similar, or lower, SES as compared with US-born members of their same racial/ethnic group.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that offspring of foreignborn mothers in the United States have different patterns of birth outcomes such as birth weight, preterm delivery, and birth defects (Harris and Shaw, 1995;Velie et al, 2006;Zhu et al, 2006;Acevedo-Garcia, et al, 2007;Ramadhani et al, 2009;Li et al, 2010;Osypuk et al, 2010). To understand what might underlie these differences, it is important to examine how patterns of risk factors for poor pregnancy outcomes differ by maternal nativity status.…”
Section: Introductionmentioning
confidence: 99%